A New Method for the Synthesis of 1-(1-Isocyanoethyl)adamantane - Dmitry Pitushkin; Gennady Butov (Molbank, 2024)
A novel single-step method has been developed for the synthesis of 1-(1-isocyanoethyl)adamantane from 1-(1-adamantylethyl)amine, chloroform, and t-BuOK, in a dichloromethane/tert-butanol (1:1) medium, yielding 92%, which is 27% higher compared to the known method, without the use of highly toxic compounds. The product was characterized using 1H and 13C NMR spectroscopy, GC-MS, and elemental analysis.